DESCRIPTION OF POST-TRAUMATIC STRESS DISORDER IN TSUNAMI NATURAL DISASTER VICTIMS IN ASIA: A SCOPING REVIEW - Lintang Arum, Silviana; Nur Alfian, Ilham; Putri Pijar, Briliani; Rahma Pratiwi, Aida (PT. Antis International Publisher, 2025)
Objective: This study aims to provide an in-depth understanding of the psychological impact of tsunamis, particularly focusing on Post-Traumatic Stress Disorder (PTSD), and to assist in developing effective interventions to support mental recovery for disaster victims. Method: A scoping review methodology was employed to examine the literature on PTSD caused by tsunamis in Asia. Relevant studies were identified through the Web of Science database using the keywords